Grak Ompimpah implementation for accelerating stunting reduction in Padasuka Village - Putri, Riva Ananda; Putri, Jihan Nabilah (Universitas Pendidikan Indonesia, 2024)
This article explores the Cimahi People's Movement to Sort Waste (Grak Ompimpah), a community program endorsed by the Cimahi City government. Aligned with environmental health, a key stunting risk factor, the initiative targets stunting reduction in the Padasuka Village area. It can be the first step in accelerating the reduction of stunting rates, especially in the Padasuka Village area. Through this program, the government expects the emergence of public awareness in carrying out a clean lifestyle, especially in daily waste management behavior. With proper waste management, a cleaner and healthier environment will be created. These changes can certainly have a good impact, especially on children's health, which will also impact the child development process. The method used in writing this article is a qualitative research method with a descriptive case study approach which aims to provide an overview or description of the implementation of the Grak Ompimpah program in the RW 20 area of Padasuka Village. Analysis reveals the program's success in fostering a healthier environment. In conclusion, prioritizing environmental health is crucial in accelerating stunting reduction efforts, with effective waste management representing a tangible starting point.